Matrix metalloproteinases and psychosocial factors in acute coronary syndrome patients - Fernandez Machulsky, Nahuel Hernan (2016)
Psychosocial factors have been linked to cardiovascular diseases independently of traditional risk factors. The impact of psychosocial factors on plaque destabilizing factors, such as matrix metalloproteinases (MMPs) has been proposed although scarcely studied. Objective: To evaluate the relationships between hostility, perceived stress and social support with MMPs activity in patients after an Acute Myocardial Infarction (AMI). Methods: Blood samples were obtained from 76 patients on admission, post-angioplasty, 24. h, 7 days and 3 months after AMI. Hostility, perceived stress and social support were evaluated by validated questionnaires. Results: Social support was positively correlated with patientś ejection fraction (r = 0.453, p = 0.009). Patients with higher infarct size presented increased MMP-2 activity at admission (p = 0.04). Patients with one diseased vessel had more social support than those with three diseased vessels (p = 0.05). The highest values of MMP-2 and MMP-9 activity were observed at the acute event, decreasing, with the lowest activity at 3 months post-AMI (p < 0.001). Only in patients with low social support, hostility correlated with MMP-2 activity, from AMI onset (r = 0.645, p = 0.013), to 7 days post AMI (r = 0.557, p = 0.038). Hostility explained up to 28% of the variance in MMP-2 activity (R2=0.28, p = 0.005). Finally, in patients with high hostility, MMP-9 was positively correlated with IL-1β (r = 0.468, p = 0.02). Conclusions: This study adds weight to the idea that two psychosocial factors, namely hostility and social support, acting jointly, may affect MMP-2 activity. Moreover, in hostile patients, there is a link between IL-1β and MMP-9. These findings support the role of psychosocial factors in plaque destabilization and in the inflammatory process in AMI.